DESIGNING THE MARKETING MIX TO INCREASE SALES (CASE STUDY AT DAPUR NONA GELIS) - Lovely Hilary Limawan; Wirawan ED Radianto (Antis Publisher, 2024)
Objective: This study aims to develop a marketing model based on the 11P Marketing Mix concept (Product, Price, Place, People, Promotion, Process, Packaging, Physical Evidence, Promise, Programming, and Partnership) to increase sales at Dapur Nona Gelis, a catering business experiencing declining turnover. Method: The research employs a qualitative method with a quasi-qualitative (post-positivistic) design. Data were collected through purposive sampling, targeting consumers, competitors' consumers, internal staff, and experts. Data collection techniques included interviews, observation, and documentation, with data validity ensured through source triangulation. Results: The study presents a comprehensive 11P Marketing Mix model emphasizing Product Quality, Affordable Pricing, Product Accessibility, Effective Public Relations, Excellent Service and Motivation, Streamlined Sales Processes, Clean Production Processes, Attractive Packaging, Reliability, Active Event Participation and Discount Programs, and Strategic Partnerships with influencers and collaborators. Novelty: This research introduces a tailored 11P Marketing Mix framework as an innovative strategy to revitalize sales performance in the catering industry, offering a holistic and practical marketing approach adaptable for similar businesses facing declining sales.